New Trick for Removal of Intravascular Retained Foreign Body: A Case Report and Review of Literature. (January 2014) - Mousa, Albeir Y.; Gill, Gurpreet; AbuRahma, Ali F.
A 54-year-old male presented to the vascular service for an urgent inpatient consultation. During an infusaport removal, the catheter was accidentally disconnected and lost intravascularly within the left subclavian vein, with the tip still in the right ventricle. We report on a novel technique for removing such intravascular foreign bodies (FBs), which will add a valuable technical option to our existing armamentarium regarding intracorporeal FB removal.